A graphene rheostat for highly durable and stretchable strain sensor. Issue 3 (18th August 2019) - Ren, Jing; Zhang, Wenjun; Wang, Yubo; Wang, Yaxiong; Zhou, Jun; Dai, Liming; Xu, Ming
Abstract: Strain sensors for human health monitoring are of paramount importance in wearable medical diagnostics and personal health monitoring. Despite extensive studies, strain sensors with both high durability and stretchability are still desired, particularly with the stability for different environmental conditions. Here, we report a series of strain sensors possessing the graphene network with a high density of intermittent physical interconnections, which produces the relative resistance change by varying the overlap area between the neighboring graphene sheets under stretching and releasing, analogous to the slide rheostat working in electronics. Our in‐situ transmission electron microscope observation reveals the full recoverability of the structure from large deformation upon unloading for ensuring the exceptional cycle stability of our material on monitoring full‐range body movements. The stable response is also demonstrated over wide temperature range and frequency range, because the peculiar dynamic structure can be maintained through the self‐adjustment to the thermal expansion of the bulk material. Based on the working mechanism of graphene "slide rheostat, " the sensing properties of the strain sensor are tailored by tuning the graphene network structure with different mass densities using different concentrations of graphene oxide dispersion, while the stretchability and sensitivity can be separately optimized for different application requirements. Abstract : Strain sensor based on partially overlapped graphene sheets produces the relative resistance change by varying the overlap area between the neighboring graphene sheets under stretching/releasing, which is confirmed by in‐situ transmission electron microscope observation. The slide rheostat design of graphene provides the exceptional cyclic stability and stable response over wide temperature and frequency range for monitoring full‐range body movements.